1997
DOI: 10.1128/jcm.35.6.1473-1476.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incubation time and buffer concentration on in vitro activities of antifungal agents against Candida albicans

Abstract: Nine selected isolates of Candida albicans were tested for their susceptibilities to amphotericin B and fluconazole by using three methods to assess the effect of incubation time and buffer concentration. By using a microdilution method with 0.0165 M 3-(N-morpholino)propanesulfonic acid (MOPS) and a 24-h incubation time, all of the isolates were found to be susceptible to amphotericin B and fluconazole. After 48 h of incubation, all isolates were still susceptible to amphotericin B. Seven of the nine isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…For those tests read spectrophotometrically, it is likely that this corresponds better to a 50% rather than an 80% decrease in OD. Many have observed that a 48-h incubation time increases the likelihood that an isolate will demonstrate a trailing effect and a higher MIC [2,3,8]. Furthermore, the data presented here show that this phenomenon appears to be species speci®c (Tables 3, 4, 6).…”
Section: Azolessupporting
confidence: 59%
“…For those tests read spectrophotometrically, it is likely that this corresponds better to a 50% rather than an 80% decrease in OD. Many have observed that a 48-h incubation time increases the likelihood that an isolate will demonstrate a trailing effect and a higher MIC [2,3,8]. Furthermore, the data presented here show that this phenomenon appears to be species speci®c (Tables 3, 4, 6).…”
Section: Azolessupporting
confidence: 59%
“…Nevertheless, these differences were not significant (P > 0AE05) when the amount of substance is expressed in lmol ml )1 (concentration units) of each compound, suggesting that the sugar moiety does not contribute to the antibacterial effect. Bacteriostatic, bactericidal or bacteriolytic effects of antibacterial substances on target cells depend on incubation period and bacterial inoculum con-centration (Tornatore et al 1997). The inoculation size in photometric assay was 20-fold greater (because of photometric measurements) than that proposed by the National Committee for Clinical Laboratory Standards (NCCLS 1999), that is the reason why the substances were assayed at concentrations nearly 20-fold MICs (Hartzen et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some Candida isolates do not show trailing effects after 24 hours of incubation but do after 48 hours. [67][68][69] Often, these isolates, called low-high MIC phenotype isolates, are susceptible after 24 hours of incubation (fluconazole MICs ≤ 8 µg/ml) but appear resistant after 48 hours (fluconazole MICs ≥ 64 µg/ml). Of interest, low-high MIC phenotypes isolated from HIV-infected patients with oropharyngeal candidiasis appeared to respond clinically to fluconazole, similar to patients infected with susceptible yeasts.…”
Section: Candida Speciesmentioning
confidence: 99%
“…71 Some investigators found decreased trailing with a medium of lower pH. 69,72,73 Adjustment of medium pH could be considered to eliminate trailing among Candida sp with azole susceptibility testing.…”
Section: Candida Speciesmentioning
confidence: 99%